2013
DOI: 10.1017/s0022215113002193
|View full text |Cite
|
Sign up to set email alerts
|

Disseminated rhinosporidiosis

Abstract: This is the first reported case of truly disseminated rhinosporidiosis with simultaneous involvement of multiple anatomically unrelated sites in a single patient. This is also the first reported case of cystic rhinosporidiosis. The possibility and sequelae of spontaneous regression of rhinosporidiosis are also discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 8 publications
1
13
0
Order By: Relevance
“…In our series, the peak age of incidence was in the second to fourth decade of life which is the active working age group which Baliga and Naik. 10 There is a male predominance in our series of 2.7:1 which is similar to the report by Bandyopadhyay et al 6 Recurrence is reported to be high by earlier authors because of previous practice of conventional surgery which lacked the precision of endoscopic localization of the rhinosporidiosis stalk at primary surgery, hence the problem of leaving behind residual disease which leads to post-operative seeding which can be eliminated by present technique of endoscopic assisted surgery and meticulous cauterization of pedicle at its attachment to the nasal mucosa and also ensures through removal of primary disease which along with regular endoscopic follow-up is the only surety for preventing long term recurrences. Treatment of rhinosporidial lesions is mainly surgical.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In our series, the peak age of incidence was in the second to fourth decade of life which is the active working age group which Baliga and Naik. 10 There is a male predominance in our series of 2.7:1 which is similar to the report by Bandyopadhyay et al 6 Recurrence is reported to be high by earlier authors because of previous practice of conventional surgery which lacked the precision of endoscopic localization of the rhinosporidiosis stalk at primary surgery, hence the problem of leaving behind residual disease which leads to post-operative seeding which can be eliminated by present technique of endoscopic assisted surgery and meticulous cauterization of pedicle at its attachment to the nasal mucosa and also ensures through removal of primary disease which along with regular endoscopic follow-up is the only surety for preventing long term recurrences. Treatment of rhinosporidial lesions is mainly surgical.…”
Section: Discussionsupporting
confidence: 90%
“…Das 5 reported an incidence of 70% affecting nasal mucosa, 15% involvement of conjunctiva and 3% involvement of urethral mucosa and only one patient in their series had disseminated disease with previous history of nine operations in their series of 96 patients reported from Bankura district of West Bengal, India. The incidence of disseminated rhinosporidiosis is extremely rare Bandyopadhyay et al 6 Das 5 reported 31 cases of 7 Sudarshan et al, 8 and Mukherjee et al 9 The disease is reported throughout the year as reported by Baliga and Naik 10 and Bandyopadhyay et al 6 and does not show any seasonal variation as reported by Paul et al 11 from Jammu. In our series, the peak age of incidence was in the second to fourth decade of life which is the active working age group which Baliga and Naik.…”
Section: Discussionmentioning
confidence: 87%
“…It appears that, like tuberculosis, rhinosporidiosis can affect any organ system which might not necessarily be anatomically contiguous [9]. However, most reports in recent years, evident from the PubMed/MEDLINE Ò search with the keyword ''rhinosporidiosis'', are single case descriptions at unusual, extranasal sites with varied and atypical presentations.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] Previously reported cases of multicentric head and neck rhinosporidiosis have mentioned the simultaneous involvement of skin across various anatomic sites such as muscle, external genitalia, urethra, and/or bone in the same patients. 10,11 These were the cases of disseminated rhinosporidiosis.…”
Section: Discussionmentioning
confidence: 99%